Blockchain & Sistem Informasi Akuntansi (B-SIA): Tinjauan Sistematis terhadap Transparansi dan Keamanan Data - Sri Intan Purnama (Universitas La Tansa Mashiro, 2025)
Blockchain technology has gained increasing attention in the field of accounting due to its potential to enhance the security, transparency, and efficiency of accounting information systems (AIS). The main issues in conventional AIS include vulnerability to data manipulation, limited transparency, and delays in auditing and reporting processes. This study aims to analyze the contribution of blockchain to improving the security, transparency, and efficiency of AIS, while also identifying its challenges and potential solutions. The research employed a systematic literature review approach following the PRISMA guidelines, with relevant articles collected from Google Scholar using specific keywords related to blockchain and accounting. After a rigorous screening process, nine high-quality and relevant articles were selected for analysis. The findings indicate that blockchain provides a high level of encryption, prevents data manipulation, supports continuous auditing, and accelerates transactions through the implementation of smart contracts. Furthermore, blockchain’s decentralized and transparent nature allows stakeholders, including auditors and regulators, to verify transactions in real time, thereby enhancing accountability. Nevertheless, several challenges remain, such as scalability issues, high implementation costs, integration with existing systems, and regulatory uncertainty across countries. Proposed solutions include developing alternative consensus mechanisms, strengthening human resource capacity through training, and establishing clearer regulatory frameworks. In conclusion, blockchain holds significant potential to revolutionize AIS by enhancing security, transparency, and efficiency. However, its successful adoption requires well-prepared implementation strategies, as well as adequate regulatory and infrastructural support.